Swine Influenza Virus Infection Decreases the Protective Immune Responses of Subunit Vaccine Against Porcine Circovirus Type 2 - Sun, Yuhang; Zhang, Jinlong; Liu, Zixuan; Zhang, Ying; Huang, Kehe (Frontiers in Microbiology, 2021)
Porcine circovirus type 2 (PCV2) is the primary pathogen of porcine circovirus diseases and porcine circovirus associated diseases. Immunization with vaccine is considered as an effective measure to control these diseases to date. However, it is still unknown whether PCV2 vaccines have protective immune responses on the animals infected with swine influenza virus (SIV), a pandemic virus in swine herds. In this study, we first compared the effects of 2 different PCV2 vaccines on normal mice and the SIV-infected mice, respectively. The results showed that these 2 vaccines had the protective immune responses on normal mice, and the subunit vaccine (vaccine S) had better effects. However, the inactivated vaccine (vaccine I) instead of vaccine S exhibited more immune responses on the SIV-infected mice. Noticeably, SIV infection significantly decreased the immune responses of vaccine S in varying aspects including decreased PCV2 antibody levels and increased PCV2 replication. Mechanistically, further studies showed that SIV infection increased IL-10 expression and M2 macrophage percentage, but decreased TNF-α expression and M1 macrophage percentage in the mice immunized with vaccine S; on the contrary, macrophage depleting by using clodronate-containing liposomes significantly alleviated the SIV infection-induced the decrease in the protective immune responses of vaccine S against PCV2. Taken together, our study indicated that SIV infection decreased the protective immune responses of vaccine S against PCV2, and the macrophage polarization induced by SIV infection might facilitate the decreased immune responses of vaccine S, which provides a new insight into vaccine evaluation and a reference for the analysis of immunization failure.